Diction in Emily Dickinson’s Poems - Yossi M Passandaran (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2019)
Diction is word choice. In poetry, the diction is commonly used by the poet. This research aims to find a description of the characteristics and uses of diction in poetry-poem by Emily Dickinson. From this description, it will be seen how Emily Dickinson in choosing words to pour her imagination into a poem. Using qualitative methods and librarian technique, the data will be analysed by describing the words included in diction that is based on: (1) the connotation and denotation meaning, (2) the general and specific meaning, (3) the use of words from other languages, and (4) the style of language. As the sample data, use four poems by Emily Dickinson, namely: "A Bird Came Down", "Faith", "Hope Is The Hope Is Thing With Feathers" and "I'm Nobody! Who Are You ". The fourth of these poems will be analyzed based on the four types of diction. From the results of the study found three types of use of diction, i.e. connotation—denotation meaning, specific—general meaning, and the use of the style language. A third using of diction is most widely found in the poem entitled "I'm Nobody! Who Are You? ". Keywords: poetry, diction, and diction characteristics